Auditory Pitch Perception in Autism Spectrum Disorder Is Associated With Nonverbal Abilities. (November 2017) - Chowdhury, Rakhee; Sharda, Megha; Foster, Nicholas E. V.; Germain, Esther; Tryfon, Ana; Doyle-Thomas, Krissy; Anagnostou, Evdokia; Hyde, Krista L.
Atypical sensory perception and heterogeneous cognitive profiles are common features of autism spectrum disorder (ASD). However, previous findings on auditory sensory processing in ASD are mixed. Accordingly, auditory perception and its relation to cognitive abilities in ASD remain poorly understood. Here, children with ASD, and age- and intelligence quotient (IQ)-matched typically developing children, were tested on a low- and a higher level pitch processing task. Verbal and nonverbal cognitive abilities were measured using the Wechsler's Abbreviated Scale of Intelligence. There were no group differences in performance on either auditory task or IQ measure. However, there was significant variability in performance on the auditory tasks in both groups that was predicted by nonverbal, not verbal skills. These results suggest that auditory perception is related to nonverbal reasoning rather than verbal abilities in ASD and typically developing children. In addition, these findings provide evidence for preserved pitch processing in school-age children with ASD with average IQ, supporting the idea that there may be a subgroup of individuals with ASD that do not present perceptual or cognitive difficulties. Future directions involve examining whether similar perceptual-cognitive relationships might be observed in a broader sample of individuals with ASD, such as those with language impairment or lower IQ.